Młodopolskie „Kontrasty" Loli Szereszewskiej - Wojkiewicz, Rozalia (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
Scarce information survives to this day about the life and work of Lola (born Leonia) Szereszewska née Rotbard, a Polish-Jewish poet. The article presents the effects of extensive discovery research and new biographical information about the poet and her family. It also characterises the key themes of the imagination presented in Kontrasty (Contrasts) – a collection of short prose poems published in 1917, inspired by the Young Poland period.